2010
DOI: 10.1007/s00056-010-1004-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorders in German and Chinese Adolescents

Abstract: Our study reveals obvious differences in the prevalence of TMD between adolescents of different ethnic origins (Asians and Europeans). These differences cannot be attributed to cultural differences alone, which implies the involvement of genetic factors in the etiology of TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
1
32
0
3
Order By: Relevance
“…In a Swedish study, pain in the lower back, neck, shoulders, elbows and hands was more frequent among Sami (northern Scandinavian indigenous) men and women compared with the general Swedish population; however, this may be owing to occupational differences [18]. In a German study, the prevalence of temporomandibular disorders (TMD), according to the Research Diagnostic Criteria for TMD (RDC/TMD), was examined in adolescent German and Chinese young women, the authors found that after controlling for relevant factors, the prevalence of RDC/TMD pain diagnoses were increased in Chinese participants as compared with German participants [19]. …”
Section: Clinical Pain/laboratory Pain Studiesmentioning
confidence: 99%
“…In a Swedish study, pain in the lower back, neck, shoulders, elbows and hands was more frequent among Sami (northern Scandinavian indigenous) men and women compared with the general Swedish population; however, this may be owing to occupational differences [18]. In a German study, the prevalence of temporomandibular disorders (TMD), according to the Research Diagnostic Criteria for TMD (RDC/TMD), was examined in adolescent German and Chinese young women, the authors found that after controlling for relevant factors, the prevalence of RDC/TMD pain diagnoses were increased in Chinese participants as compared with German participants [19]. …”
Section: Clinical Pain/laboratory Pain Studiesmentioning
confidence: 99%
“…It was reported that 14.9%–17.9% of Chinese people suffered from TMD [2, 3]. The causative factors for the various signs and symptoms of TMD are multifactorial and related to psychological, functional and structural features [4].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19] Besides sensory and pain 4 responses, ethnic differences also exist regarding motoric reflex responses in the trigeminal region. [19] Furthermore, in a recent study [20], the prevalence of TMD pain was higher among Asian than European people.…”
Section: Introductionmentioning
confidence: 94%